Validation of the Malay version of the parental bonding instrument among Malaysian youths using exploratory factor analysis - Muhammad N.A.; Shamsuddin K.; Omar K.; Shah S.A.; Amin R.M. (Malaysian Journal of Medical Sciences, 2024)
Background: Parenting behaviour is culturally sensitive. The aims of this study were (1) to translate the Parental Bonding Instrument into Malay (PBI-M) and (2) to determine its factorial structure and validity among the Malaysian population. Methods: The PBI-M was generated from a standard translation process and comprehension testing. The validation study of the PBI-M was administered to 248 college students aged 18 to 22 years. Results: Participants in the comprehension testing had difficulty understanding negative items. Five translated double negative items were replaced with five positive items with similar meanings. Exploratory factor analysis showed a three-factor model for the PBI-M with acceptable reliability. Four negative items (items 3, 4, 8, and 16) and item 19 were omitted from the final PBI-M list because of incorrect placement or low factor loading (< 0.32). Out of the final 20 items of the PBI-M, there were 10 items for the care factor, five items for the autonomy factor and five items for the overprotection factor. All the items loaded positively on their respective factors. Conclusion: The Malaysian population favoured positive items in answering questions. The PBI-M confirmed the three-factor model that consisted of care, autonomy and overprotection. The PBI-M is a valid and reliable instrument to assess the Malaysian parenting style. Confirmatory factor analysis may further support this finding. Penerbit Universiti Sains Malaysia, 2014.